2013
DOI: 10.3109/19390211.2013.830674
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bioactive Phytoconstituent fromAlpinia galangaL. with Anti-Hyperlipidemic Activity

Abstract: The present study was undertaken to explore the antihyperlipidemic effect of ethanolic extract of rhizomes of Alpinia galanga L. and its chloroform fraction in Triton-induced hyperlipidemic rats. Bioactivity guided fractionation was followed by chromatographic studies. Flash chromatography was done for the most active fraction resulting in the isolation of 5-(hydroxymethyl) furfural. Animals were administered with i.p. injection of Triton WR 1339 at dose of 400 mg/kg body weight. After 24 hr of Triton administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Sivakumar et al, (2010) and Sivakumar and Anuradha, (2011) showed that galangin can reduce kidney and liver injury. Also, Xia et al, (2010); Shiv Kumar and Alagawadi, (2011);Iyer et al, (2013) and Kumar and Alagawadi, (2013) showed that galangin exerted improved the liver functions and lipid profile in serum.…”
Section: Discussionmentioning
confidence: 97%
“…Sivakumar et al, (2010) and Sivakumar and Anuradha, (2011) showed that galangin can reduce kidney and liver injury. Also, Xia et al, (2010); Shiv Kumar and Alagawadi, (2011);Iyer et al, (2013) and Kumar and Alagawadi, (2013) showed that galangin exerted improved the liver functions and lipid profile in serum.…”
Section: Discussionmentioning
confidence: 97%